Operational limits on WEST inertial divertor sector during the early phase experiment. (11th January 2016) - Firdaouss, M; Corre, Y; Languille, P; Greuner, H; Autissier, E; Desgranges, C; Guilhem, D; Gunn, J P; Lipa, M; Missirlian, M; Pascal, J-Y; Pocheau, C; et al.
Abstract: The primary goal of the WEST project is to be a test bed to characterize the fatigue and lifetime of ITER-like W divertor components subjected to relevant thermal loads. During the first phase of exploitation (S2 2016), these components (W monoblock plasma facing unit—W-PFU) will be installed in conjunction with graphite components (G-PFU). Since the G-PFU will not be actively cooled, it is necessary to ensure the expected pulse duration allows the W-PFU to reach its steady state without overheating the G-PFU assembly structure or the embedded stainless-steel diagnostics. High heat flux tests were performed at the GLADIS facility to assess the thermal behavior of the G-PFU. Some operational limits based on plasma parameters were determined. It was found that it is possible to operate at an injected power such that the maximal incident heat flux on the lower divertor is 10 MW m −2 for the required pulse length.